Machine Learning in Medical Field: An Application of Auxiliary Tumor Treatment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
These years, with artificial intelligence and machine learning becoming the hotspot of research,several applications have emerged in each of these areas. It exists not only as a kind of academicfrontier but also something close to our life. In this trend, the combination of medical care andmachine learning becomes more and more tighter. The proposal of its main idea also greatlyalleviated the existing situation of unbalanced medical distribution and resources strain. This papersummarizes some application of machine learning and auxiliary tumor treatment in the process ofmedical resource allocation and puts forward some new methods of application to realize it closer tohuman life in the era of artificial intelligence and the explores a good situation of mutual combinationof medical industry and computer industry, which is benefit both.